The Effectiveness of the Discussion Method in Improving Student Learning Outcomes in the Fiqh Subject at MTS Negeri 2 Indramayu - Arif Rahmat Riyadi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2022)
The purpose of this study was to find out whether the application of the discussion method could improve student learning outcomes in the subject of Fiqh class IX A MTS Negeri 2 Indramayu. This type of research is the Mixed Method method, which is a combination of qualitative and quantitative methods. Mixed method is a method that uses a combination of research procedures, where one method is more dominant than the other. Less dominant methods are only positioned as complementary methods as additional data. The conclusion of this study is that the implementation of the application of the Discussion learning method in Fiqh subjects has a positive influence in increasing students' learning interest. it can be concluded that the discussion method proved to be very effective for increasing motivation and learning outcomes. This can be seen in the observation scores obtained for class IX A at MTs Negeri 2 Indramayu in cycle I, namely (58.3%) and the results of the test, namely (54.84%) students who passed. In cycle II, there was a significant increase in class observation scores (80.5%) and the test results (87.10%) of students who passed in the high category because they exceeded the KKM standards carried out at MTs Negeri 2 Indramayu.